(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2013)
بعيداً عن الأطر الجغرافية، التي تحبس المفاهيم والأفكار والمضامين العقائدية في رقعة جغرافية واحدة، فإننا نرى، أن الأنا كما الآخر، ليس رقعة جغرافية، وإنما نحن ننظر إلى الأنا باعتبارها مجموعة القيم الأصيلة، والمبادئ العليا. حينما نستخدم مصطلح الأنا أو الذات فإن المقصود من ذلك هو القيم المعيارية المتعالية على الزمان والمكان مع تجربة إنزال تلك القيم المعيارية المطلقة على الواقع النسبي والمتحرك والمتغير. وتتحدد دلالات الغير بكل وضوح وجلاء في الخطاب الفلسفي الحديث والمعاصر عندما نستحضر الصراعات الموجودة حاليا بين الأفراد والشعوب والإثنيات والعرقيات والأقليات...، وكذلك حينما نستدعي ما يسمى بالتطهير العرقي، والتمييز العنصري، وصراع الحضارات (صامويل هنتغتون)، ونهاية التاريخ (فوكو ياما). من هنا فإن وعي الآخر وعياً موضوعياً ونقدياً، سيكون أحد المحفزات الأساسية لاكتشاف الذات فكراً وقيماً وأنماطاً حضارية. وصفوة القول، أننا لا ندعو إلى مواءمة بين الأنا والآخر، وإنما ندعو إلى بلورة الأطر المناسبة للإفادة المتبادلة عن طريق الحوار والتفاهم المشترك بين الأنا والآخر. ستحاول الدراسة طرح جملة تساؤلات والإجابة عنها، رغم أن الباحث لا يمتلك أجوبة قاطعة على الأسئلة التي أثارَ الجدل حولها، بل يمتلك فقط شجاعة إبداء الرأي في هذه الأجوبة، ومحاولة تقديم إجابات تحتاج بدورها إلى إغناء مستمر. This study will attempt to put questions and answer them, although we do not have conclusive answers to the questions raised by the controversy around, but we have the courage to express an opinion on these answers, and try to provide answers in turn need to constantly enrich. Away from geographical frameworks, which hold its concepts, ideas and ideological content in a single geographical area, we see, that the ego as the other, is not a geographical area, but we look to the ego as a set of inherent values, and higher principles. When we use the term ego or self, we mean the normative values ​​transcendent of time and place with the experience of the infliction of normative values on ​​relative absolute reality, mobile and variable. So, the semantics of the other are clearly determined in the modern and contemporary philosophical discourse. Also when we evoke conflicts existing between individuals and peoples, ethnicities and ethnic minorities ... and also when we recall the so-called ethnic cleansing, racial discrimination, and the clash of civilizations (Samuel Huntington), and the end of history (Foucault Yama). Hence, the awareness of the other conscious objective and critical, it will be one of the main catalysts for self-discovery of thought, values ​​and cultural patterns. In short, we do not call for harmonization between the ego and the other, but a call to develop appropriate frameworks for mutual benefit through dialogue and mutual understanding between the ego and the other.